Floriaster maya Downey 1980 - Mah, Christopher L. (Zenodo, 2020)
Floriaster maya Downey 1980 Figure 11 A–E Comments Floriaster maya has only previously been known from the type locality at the southern end of the Yucatan Channel. These observations are the first in situ observations of this species and represent new occurrence records outside of the type locality. This species was recognized by the triangular arms (Fig 11C), prominent pointed tubercles on the marginal plate series (Fig. 11E), the granular covering on the abactinal disk surface and the rugose granules and spines present on the actinal plate surface (Fig. 11E). Adambulacral pedicellariae abundance is higher in the collected specimen (USNM 1607582) but in all other respects, the specimen is nearly identical to the holotype. Feeding Observations Of the four observations of this species, two observations showed this species perched vertically on what appear to be dead Lophelia corals (Fig. 11A) with a second feeding observation showing an individual perched on a bamboo coral stalk (Isididae) (Fig. 11B). This likely indicates feeding by Floriaster on the polyps of the coral, but could also be feeding on epizoites, such as hydroids or other organic film, growing on the dead skeletons. Occurrence: Mona South Ridge , Berg Bits, off Southeastern United States, southern end of Yucatan Channel. 933– 1156 m . Images Examined Mona South Ridge, 17.947047, -67.888323, 1156 m EX1811_IMG_20181117T 150413 Z_ROVHD.jpg (feeding) Berg Bits off SE United States 23.983814, -83.38658, 960 m, EX1907_IMG_20191119T145056Z_ROVHD. jpg Berg Bits off SE United States, 23.983228, -83.392675, 932 m, EX1907_IMG_20191119T183826Z_ROVHD. jpg Material Examined USNM 1607582 Berg Bits, off SE United States. 23.9832, -83.3927, 929 m Coll. ROV Deep Discoverer , NOAA Ship Okeanos Explorer , 19 Nov 2019, 1 wet spec. R=3.6 r=1.7. EX1907_IMG_20191119T160037Z_ROVHD.jpg : Published as part of Mah, Christopher L., 2020, New species, occurrence records and observations of predation by deep-sea Asteroidea (Echinodermata) from the North Atlantic by NOAA ship Okeanos Explorer, pp. 201-260 in Zootaxa 4766 (2) on pages 226-228, DOI: 10.11646/zootaxa.4766.2.1, http://zenodo.org/record/3764018 : {"references": ["Downey, M. E. (1980) Floriaster maya, new genus and species of the family Goniasteridae (Echinodermata: Asteroidea). Proceedings of the Biological Society of Washington, 93, 346 - 349."]}